Soft computing in data science : third International Conference, SCDS 2017, Yogyakarta, Indonesia, November 27-28, 2017, Proceedings /: third International Conference, SCDS 2017, Yogyakarta, Indonesia, November 27-28, 2017, Proceedings. (2017) - Unknown
No abstract available